(untitled) (Eurasian Research Bulletin, 2022)
History has shown that for centuries, the science of law has been in the guise of poetry. The source of the power of law was also the passionate and magical word that bursts from the net of the soul. According to Plato’s definition, law was born in the form of hymns, which are a gift from the divinity. The Avesto is in the form of divine hymns. The sermons and fards in the Qur’an, the prophecies, the Shari’ah and the rules of morality are written in hymns, just as in the Bible. The search was carried out by many: great writers of the past, as well as anonymous authors of folk tales, fairy tales and legends. Among them are the geniuses of Alisher Navoi and Alighieri Dante, Erasmus of Rotterdam and William Shakespeare, Umar Khayyam and Friedrich von Schiller, Fyodor Dostoevsky and Leo Tolstoy, there are many other great names. Goethe has a special place among these representatives of world literature.